The Strength and Thermal Properties of Concrete containing Water Absorptive Aggregate from Well-Graded Bottom Ash (BA) as Partial Sand Replacement - Abdullah M.J.; Beddu S.; Manan T.S.B.A.; Syamsir A.; Naganathan S.; Mohd Kamal N.L.; Mohamad D.; Itam Z.; Yee+ H.M.; Mohd Yapandi M.F.K.; Mohamed Nazri F.; Shafiq N.; et al. (Elsevier Ltd, 2023)
Ash handling; Ashes; Bending strength; Concrete aggregates; Concrete mixers; Concrete mixtures; Sand; Tensile strength; Thermal conductivity; Thermal Engineering; Thermoelectric power plants; Water absorption; Bottom ash; Engineering properties; Fine aggregates; High water; Maximum strength; Partial sand replacement; Properties of concretes; Replacement materials; Split tensile strengths; Well-graded bottom ash; Compressive strength